Deteksi Kasus Fraud Di Indonesia: Peran Digital Forensic Dan Big Five Personality Auditor Dalam Kerangka Hexagon Fraud Theory - Ischaq, Maulana; Setyahuni, Suhita Whini; Zhafira, Aqila Azza; Syahputri, Naesila Yulyana Saskia; Syafira, Atina Nur Azumi; Kurniawan, Maulana Bintang Arie (JURNAL MANAJEMEN DAN BISNIS, 2025)
Purpose – This study aims to analyze the role of digital forensics and the Big Five Personalities of auditors in uncovering fraud cases within the framework of Hexagon Fraud Theory. The research focuses on large-scale corruption cases in Indonesia. Novelty – This study's novelty lies in the simultaneous examination of the Big Five Personalities and Hexagon Fraud Theory on auditors' ability to detect fraud. Furthermore, this study adds the role of digital forensics as a moderating variable, distinguishing it from previous studies that tend to examine these variables separately. Method – This study uses a quantitative approach with primary data obtained from an online questionnaire. The analysis technique used is Structural Equation Modeling (SEM) with Smart-PLS software to examine the relationships between the variables studied. Findings – The results show a positive and significant relationship between openness to experience and auditors' ability to detect fraud. Furthermore, the variables rationalization, capability, and ego also play an important role in enhancing auditors' abilities. Meanwhile, other variables showed no significant effect. Limitations and Implications – This research is limited to public auditors in Public Accounting Firms (KAP) and inspectorates in Indonesia, so the results cannot be broadly generalized. The implications of this study can serve as a basis for academics and practitioners in understanding personality and fraud factors that influence auditor ability, considering the role of digital forensics as a moderating variable.